2022
DOI: 10.3390/cancers14020275
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Adenocarcinoma Incidence and Survival Trends in South Australia, 1990–2017

Abstract: Background & Aims: Globally, there has been a concerning rise in the incidence of young-onset cancers. The aim of this study was to provide trends in the incidence and survival of gastrointestinal adenocarcinomas (oesophagus, stomach, pancreas, and colorectal) in South Australia over a 27-year period. Methods: This is a cross-sectional analysis of a prospective longitudinal database including all cases of gastrointestinal adenocarcinomas prospectively reported to the South Australian (State) Cancer Registr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 56 publications
1
15
1
9
Order By: Relevance
“…Although the incidence of GI adenocarcinomas is on the rise, improved survival has been demonstrated in our young-onset cohort. This finding is in contrast to our observations in young-onset adenocarcinomas in South Australia (where the overall survival across all subsites has remained unchanged) [ 5 ]. This trend has been attributed to the significantly improved survival in colonic adenocarcinoma, especially in the last time period.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although the incidence of GI adenocarcinomas is on the rise, improved survival has been demonstrated in our young-onset cohort. This finding is in contrast to our observations in young-onset adenocarcinomas in South Australia (where the overall survival across all subsites has remained unchanged) [ 5 ]. This trend has been attributed to the significantly improved survival in colonic adenocarcinoma, especially in the last time period.…”
Section: Discussioncontrasting
confidence: 99%
“…Globally, there have been several reports of increasing incidence of early- or young-onset cancers [ 1 , 2 , 3 , 4 ]. Recently, we confirmed this disturbing trend over the past 28 years in South Australia by interrogating data from the South Australian Cancer Registry [ 5 ]. Early life events have long been suspected to play a role in the causation of young-onset cancers [ 6 , 7 ].…”
Section: Introductionsupporting
confidence: 56%
“…Recently, we interrogated the South-Australian Cancer Registry data over the last 3 decades, and reported that there has been a steady increase in the incidence of pancreatic adenocarcinoma amongst individuals less than 50 years of age [8]. Ansari et al [9], too, reported similar findings from the USA.…”
mentioning
confidence: 77%
“…Dank der Vorsorgekoloskopie haben in Deutschland in den letzten 20 Jahren die altersstandisierten Neuerkrankungen um mehr als 20 % und die Darmkrebstodesfälle bei den über 55-Jährigen um mehr als 35 % abgenommen [42]. Es erkranken nun aber immer mehr junge (< 50 Jahre) Erwachsene [17,32,43 Datenquelle: [33].…”
Section: Darmkrebsunclassified
“…Generell erkranken nun mehr und mehr junge Erwachsene (< 50 Jahre) an Prädiabetes-bzw. T2D-assoziierten Malignomen [17,32], einschließlich des Magenkardiakarzinoms [6,12,14] (▶ Abb. 1).…”
Section: Adenokarzinome Der Speiseröhre Und Des Magensunclassified